Absences, exclusivities and utopias: Afrikaans film as a cinema of political impotence, 1994 - 2014 - Broodryk, Chris Willem (Centre for Film and Media Studies, 2016)
This thesis develops a conceptual and theoretical framework within which to position contemporary Afrikaans cinema as a cinema of political impotence. Afrikaans cinema is first located within the tensions of democratic post-transitional South African society and linked to the identity politics of being identified as 'Afrikaner' or 'Afrikaans speaking'. The thesis provides a critical overview of film scholar Thomas Elsaesser's studies of (New) German Cinema and Hollywood, identifying key notions such as double occupancy to inform the study's vocabulary, and discussing how certain cultures have responded to traumatic events in which they were complicit. The thesis then links Elsaesser's studies to Fredric Jameson's views on political cinema and the political failures of postmodernism. This conceptual and theoretical framework identifies and problematises the neoliberal structures that guide much of Afrikaans filmmaking, and offers a historical overview of key moments and figures in South African (primarily Afrikaans) filmmaking in order to demonstrate that there Afrikaans cinema.